Aerobic granular sludge process treats real fish canning wastewater. - Paulo, A. M. S. (2018)
Aerobic Granular Sludge (AGS) is an innovative technology used for carbon and nutrients removal from wastewater, using less space and energy compared to other biotechnological solutions. Aerobic granules present a compact structure, composed of extracellular polymeric substances (EPS), which increase AGS resistance to variable wastewater composition, as those commonly produced by industry. In this study, C, N and P-removal from a fish canning plant wastewater was evaluated using an AGS-SBR (sequential batch reactor). Throughout the first 3 months of operation with variable feed composition, the chemical oxygen demand (COD) at the outlet was below the discharge limit of 125 mg O2 L-1, phosphorous removal was stable and the nitrification process improved. At the higher organic loading rates (OLR), the AGS performance was temporary affected. This study contributes to understanding the effects of the variability of a real wastewater on an AGS process.